Nature recruit and its implications in interior environment - Radi, Hussein Alaa; Lafta, Raja Saedi (Al-Adab Journal, 2021)
Researchers have increased interest in studying nature because it is the first, inspiring and manageable teacher from which man draws over time to solve any problem, so the designer is inspired by its symbols and elements mostly from nature and organizes those elements in light of the various and different elements that nature possesses because it is characterized by diversity, balance, proportion and symmetry. Nature has simulated human achievements over the ages and has led them to effective structures, tools, materials, mechanisms, processes, methods and systems.